A Competency Model of Psychology Practice: Articulating Complex Skills and Practices - von Treuer, Kathryn Maree; Reynolds, Nick (Frontiers in Education, 2017)
As in all professions, the practice of psychologists is based on the acquisition and application of knowledge, skills, and behaviors that are often conceptualized as competencies. As students progress through their curricula, they might approach each individual unit as a discrete set of skills embedded in different coursework units. However, these discrete skills and competencies may not reflect the diverse, interrelated, and complex nature of the practice of psychology. This project sought to identify the key competencies required to practice psychology and to present these competencies in a model that demonstrates how melding these competencies together better reflects authentic, real-world practice. The methodology comprised two stages. Pre-existing data, including detailed postgraduate course content, graduate course evaluations, and destinations such as(i.e., vocational outcomes), from two of universities were distributed to eight Subject Matter Experts (SMEs) for consideration. During the first stage of the study, the eight SMEs engaged in a modified Delphi process designed to explore psychology competencies. The SME panel also answered several rounds of questions at (first face-to-face, and later online). From these sessions, a draft psychology competency model was developed, including both competencies that are underpinned by the scientific-practitioner process, and meta- competencies. During the second stage of the study, practitioners and academics from various areas of psychology practice participated in a series of workshops and. The results of these workshops were later used to further refined the competency model. Future research is needed to validate the model. Elucidation of competencies in psychology is imperative and has ramifications for psychology regulation, training, and practice.